The Effects of Induction and Treatment of Intracranial Hypertension on Cerebral Autoregulation: An Experimental Study - Marcelo de Lima Oliveira; Angela Macedo Salinet; Ricardo de Carvalho Nogueira; Alessandro Rodrigo Belon; Wellingson Silva Paiva; Brasil Chian Ping Jeng; Manoel Jacobsen Teixeira; Edson Bor-Seng-Shu (Neurology Research International)
Background. This study aimed to analyse cerebral autoregulation (CA) during induction and treatment of intracranial hypertension (ICH) in an experimental model. Materials and Methods. Landrace and Duroc piglets were divided into mild and severe ICH groups. Four or seven millilitres of saline solution was infused into paediatric bladder catheter inserted in the parietal lobe (balloon inflation). After 1.5 h, a 3% saline solution was infused via venous catheter, and 30 min later, the bladder catheter balloon was deflated (surgery). The cerebral static autoregulation (sCA) index was evaluated using cerebral blood flow velocities (CBFV) obtained with Doppler ultrasound. Results. Balloon inflation increased ICP in both groups. The severe ICH group showed significantly lower sCA index values (p=0.001, ANOVA) after balloon inflation (ICH induction) and a higher sCA index after saline injection (p=0.02) and after surgery (p=0.04). ICP and the sCA index were inversely correlated (r=−0.68 and p<0.05). CPP and the sCA index were directly correlated (r=0.74 and p<0.05). Conclusion. ICH was associated with local balloon expansion, which triggered CA impairment, particularly in the severe ICH group. Moreover, ICP-reducing treatments were associated with improved CA in subjects with severe ICH.